Loudness Assessment of Musical Tones Equalized in A-weighted Level - KLONARI, Despina; PASTIADIS, Konstantinos; PAPADELIS, Georgios; PAPANIKOLAOU, George (Archives of Acoustics, 2011)
The present study was carried out to determine whether recorded musical tonesplayed at various pitches on a clarinet, a flute, an oboe, and a trumpet are perceivedas being equal in loudness when presented to listeners at the same A-weighted level.This psychophysical investigation showed systematic effects of both instrument typeand pitch that could be related to spectral properties of the sounds under consideration.Level adjustments that were needed to equalize loudness well exceeded typicalvalues of JNDs for signal level, thus confirming the insufficiency of A-weighting asa loudness predictor for musical sounds. Consequently, the use of elaborate computationalprediction is stressed, in view of the necessity for thorough investigation offactors affecting the perception of loudness of musical sounds.